Efektivitas Model Pembelajaran Team Assisted Individualization (TAI) Terhadap Hasil Belajar Matematika - Simanjuntak, Parulian; Rasjid, Harun (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2019)
The purpose of this study was to study the learning model of the Assisted Individualization Team (TAI) on the mathematics learning outcomes of students of class X in the SMK Wijaya Kususma. The research method used in this study. The sample was obtained through purposive sampling, each of 30 students for two classes namely the experimental class and the control class, so that the total sample was 60 students. Data analysis using t-count test, and first performed descriptive statistical analysis and test data requirements. To test norms using the reliability test, for the homogeneity test using the Fisher test and validation test. The results of the study showed that there was the application of the Assisted Individualization (TAI) learning model to the mathematics learning outcomes.